Design and Operational Evaluation of Off-Grid Solar Power Plants with Integrated Automatic Cleaning Systems for Enhanced Performance - Akbar Abadi; Nazris Nazaruddin; Yani Kamisa Putri; Dedi Erawadi; Herisajani; Hanalde Andre; Ahmad Ilyas Putra Riancefi (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2026)
This study details the design and experimental evaluation of an off-grid photovoltaic (PV) system equipped with an automatic solar panel cleaning mechanism to address performance degradation due to dust accumulation. The system integrates a mechanical wiper-based cleaning unit, solar charge controller (SCC), inverter, and low-voltage disconnect (LVD) to maintain reliable and stable operation in stand-alone settings. Experimental tests were performed on a 50 Wp PV module under actual outdoor conditions in Padang, Indonesia. System performance was assessed before and after panel cleaning using key electrical parameters, such as output voltage, current, output power, and relative efficiency improvement. Results show that the automatic cleaning mechanism increased the average PV output power from 0.88 W to 1.71 W, representing an efficiency improvement of approximately 11.89% compared to the uncleaned state. In contrast to previous studies that focus on grid-connected systems or manual cleaning methods, this research introduces a low-cost, self-operating cleaning solution tailored for small-scale off-grid PV applications in tropical environments. The proposed system offers practical benefits for enhancing energy yield, system reliability, and maintenance efficiency in remote solar installations.